KESULITAN GURU DALAM PEMBELAJARAN TEMATIK DI SEKOLAH DASAR - Andrini Rosa Putri Siregar; Devina Santri; Rama Nida Siregar (STKIP Subang, 2025)
This study investigates the barriers faced by first-grade teachers in implementingthematic learning under the Independent Curriculum (Curriculum Merdeka). Usinga qualitative case study approach involving observation, interviews, anddocumentation, the study identified several significant challenges. In the planning stage, the main challenges included developing integrated teaching modules, as well as limited time and reference resources. During implementation, teachers faced challenges in classroom management, low student participation, a lack of learning media, and difficulty connecting teaching materials to students' real-life experiences. Furthermore, the evaluation stage was also problematic due to the difficulty of implementing continuous, authentic assessments to assess attitudes, knowledge, and skills. Administrative and time constraints also hampered optimal evaluation. To address these issues, the study recommends training, teacher mentoring, increased resources, and the implementation of more effective and contextual methods to optimize thematic learning and support holistic student development.